BeamDyn: a high‐fidelity wind turbine blade solver in the FAST modular framework. Issue 8 (14th March 2017) - Wang, Qi; Sprague, Michael A.; Jonkman, Jason; Johnson, Nick; Jonkman, Bonnie
Abstract: This paper presents a numerical implementation of the geometrically exact beam theory based on the Legendre‐spectral‐finite‐element (LSFE) method. The displacement‐based geometrically exact beam theory is presented, and the special treatment of three‐dimensional rotation parameters is reviewed. An LSFE is a high‐order finite element with nodes located at the Gauss–Legendre–Lobatto points. These elements can be an order of magnitude more computationally efficient than low‐order finite elements for a given accuracy level. The new module, BeamDyn, is implemented in the FAST modularization framework for dynamic simulation of highly flexible composite‐material wind turbine blades within the FAST aeroelastic engineering model. The framework allows for fully interactive simulations of turbine blades in operating conditions. Numerical examples are provided to validate BeamDyn and examine the LSFE performance as well as the coupling algorithm in the FAST modularization framework. BeamDyn can also be used as a stand‐alone high‐fidelity beam tool. Copyright © 2017 John Wiley & Sons, Ltd.